Digital Currency in the System of Civil Law Objects: Cryptocurrencies, Stablecoins, Central Bank Digital Currencies - Cherviakov, Mykyta (Problems of legality, 2025)
The relevance of the article lies in the proposed approach: to classify digital objects not only by legal status but also by functional features. The need for such an approach arises from legal uncertainty in Ukraine caused by the absence of a special law on virtual assets and the fragmented regulation of digital things and money. The purpose of the article is to doctrinally formulate the category of “digital currency” as an inter-category concept encompassing cryptocurrencies, stablecoins, and central bank digital currencies. Methods: formal-legal, comparative-legal, functional, and systemic approaches; analysis of national acts and draft laws of Ukraine, European Union law, and the positions of international institutions. Results: it is proven that despite their different legal nature, these objects share common features—immaterial form, technological basis, value, transferability, the ability to perform the functions of a means of payment and a store of value, and programmability. The dual nature of digital currency is substantiated, as it combines features of property and money. The distinction between central bank digital currencies and electronic money, which should not be equated, is demonstrated. It is proposed to identify stablecoins and central bank digital currencies as a separate group of civil law objects, while cryptocurrencies, due to volatility, retain the nature of property. Prospects: development of a conceptual framework for improving the civil legislation of Ukraine in line with international standards, clarification of criteria for distinguishing digital objects, and modeling their integration into the system of civil law objects.